Negotiating intersex: A case for revising the theory of social diagnosis. (February 2017) - Jenkins, Tania M.; Short, Susan E.
Abstract: The theory of social diagnosis recognizes two principles: 1) extra-medical social structures frame diagnosis; and 2) myriad social actors, in addition to clinicians, contribute to diagnostic labels and processes. The relationship between social diagnosis and (de)medicalization remains undertheorized, however, because social diagnosis does not account for how social actors can also resist the pathologization of symptoms and conditions—sometimes at the same time as they clamor for medical recognition—thereby shaping societal definitions of disease in different, but no less important, ways. In this article, we expand the social diagnosis framework by adding a third principle, specifically that 3) social actors engage with social structures to both contribute to, and resist, the framing of a condition as pathological (i.e. medicalization and demedicalization). This revised social diagnosis framework allows for the systematic investigation of multi-directional, dynamic processes, formalizing the link between diagnosis and (de)medicalization. It also responds to long-standing calls for more contextualized research in (de)medicalization studies by offering a framework that explicitly accounts for the social contexts in which (de)medicalizing processes operate. To showcase the utility of this revised framework, we use it to guide our analyses of a highly negotiated diagnosis: intersex. Highlights: Social diagnosis draws attention to the extra-medical factors that shape diagnosis. Social diagnosis (SD) processes are multilevel, multi-directional, and dynamic. Actors and structures promote and resist pathological framing ((de)medicalization). The SD framework is revised to account for resistance to medicalization. The case of intersex is used to demonstrate the utility of the new framework.